2004
DOI: 10.1097/01.ju.0000131908.19114.d3
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Pathological and Clinical Prostate Cancer With Age: Age Related Alterations of Local Immune Surveillance

Abstract: Apparently, with aging the immune surveillance of the already immune privileged prostate is progressively and further affected. This condition may result in the inability of the gland to eradicate emergent malignant cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…Furthermore, the observed diVerence in survival between the subcutaneous and the intraprostatic challenge could also be an eVect of a blood-prostate-barrier, which is assumed to restrict the passage of leukocytes for immune surveillance of the prostate [9,12,23]. By using an immunological attractant like GM-CSF this barrier might be broken, making the prostate better accessible.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the observed diVerence in survival between the subcutaneous and the intraprostatic challenge could also be an eVect of a blood-prostate-barrier, which is assumed to restrict the passage of leukocytes for immune surveillance of the prostate [9,12,23]. By using an immunological attractant like GM-CSF this barrier might be broken, making the prostate better accessible.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The incidence of prostate cancer is rare until age 40, but increases to 30% of all males by age 50 and to 75% by age 80. 5 With extension of the average life span, it has become the most common cancer among males of the Western world accounting for 35% of all cancers. 5 In the United States and Europe, it claims the life of one in five men diagnosed with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…5 With extension of the average life span, it has become the most common cancer among males of the Western world accounting for 35% of all cancers. 5 In the United States and Europe, it claims the life of one in five men diagnosed with the disease. 6 Current treatment modalities for localized prostate cancer include surgery and radiation therapy, both of which are associated with risks of nerve damage and sexual and/or bladder dysfunction, and other complications.…”
Section: Introductionmentioning
confidence: 99%
“…and to 75% by age 80 [5]. With extension of the average life span, it has become the most common cancer among males of the Western world accounting for 35% of all cancers [5].…”
Section: -mentioning
confidence: 99%
“…Systemic toxicity induced by recombinant IL-12 administered systemically or subcutaneously for the treatment of cancer has been a major concern in many prior studies, including phase I and II trials [5][6][7]. In the present study, however, no significant increase in the levels of IL-12 in the serum was observed when measured on days 4, 6, and 10 post-treatments in the TRAMP-C2 unilateral model suggesting that the expression of IL-12 from the NV1 042 virus is a local effect and significant amounts of cytokine is not entering the systemic circulation.…”
mentioning
confidence: 99%